Introduzione: L’identità narrativa tra ermeneutica e psicoanalisi - Busacchi, Vinicio; Martini, Giuseppe (B@belonline, 2021)
Introducing the volume of Babel dedicated to the narrative identity between hermeneutics and psychoanalysis and the related contributions, the editors highlight the links in Ricœur’s work between the question of identity and the question of the subject, as well as between narrative and personal identity. The development of narrative in the psychoanalytic field from the 1980s onwards and the change that Ricœur’s contributions can give to this reflection are then briefly recalled. In particular, the relationship between the narrative, the untranslatable and the translation is enhanced. Finally, the authors mention other topical issues in the psychoanalytic field to which Ricœur’s reflection has provided a fundamental contribution: the relationship between truth and relativism, the status of the self, the role of the image.